Determining the Potential of L-Selenomethionine as a Protective Agent Against Exercise-Induced Muscle Damage - Roy Januardi Irawan; Joesoef Roepajadi; Heri Wahyudi; Nanda Rimawati; Mokhamad Nur Bawono; Ananda Perwira Bakti; Abdul Rohim Tualeka; Adi Wijayanto (Physical Education Theory and Methodology)
Background. Delayed-Onset Muscle Soreness (DOMS) is a phenomenon that arises from muscle damage following uncommon or intense eccentric exercise, with symptoms persisting  for a few days. The condition is characterized by muscle pain, reduced muscle strength, limited range of motion, and general discomfort that affects performance and disrupts the exercise program.